2008
DOI: 10.1021/jf801989e
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Kinetics of Sulforaphane in Humans after Consumption of Cooked versus Raw Broccoli

Abstract: The aim of this study was to determine the bioavailability and kinetics of the supposed anticarcinogen sulforaphane, the hydrolysis product of glucoraphanin, from raw and cooked broccoli. Eight men consumed 200 g of crushed broccoli, raw or cooked, with a warm meal in a randomized, free-living, open cross-over trial. Higher amounts of sulforaphane were found in the blood and urine when broccoli was eaten raw (bioavailability of 37%) versus cooked (3.4%, p ) 0.002). Absorption of sulforaphane was delayed when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 16 publications
(20 reference statements)
8
121
2
2
Order By: Relevance
“…Red cabbage is usually served as a fresh salad in Japan. Vermeulen et al (2008) reported on the bioavailability of sulforaphane in humans after consumption of raw or cooked broccoli; higher amounts of sulforaphane were found in the blood and urine when broccoli was eaten raw (bioavailability of 37%) versus cooked (3.4%, P = 0.002). The Japanese eat cabbage both raw and cooked, although broccoli is most often consumed cooked, which at least partly inactivates myrosinase.…”
Section: Resultsmentioning
confidence: 99%
“…Red cabbage is usually served as a fresh salad in Japan. Vermeulen et al (2008) reported on the bioavailability of sulforaphane in humans after consumption of raw or cooked broccoli; higher amounts of sulforaphane were found in the blood and urine when broccoli was eaten raw (bioavailability of 37%) versus cooked (3.4%, P = 0.002). The Japanese eat cabbage both raw and cooked, although broccoli is most often consumed cooked, which at least partly inactivates myrosinase.…”
Section: Resultsmentioning
confidence: 99%
“…Angelino et al [13] suggest that plant myrosinase is essential for an effective dose of ITC to be formed and absorbed, supporting the traditional idea that cooked Brassica are less likely to provide health benefits than uncooked vegetables. In the study performed by Vermeulen et al [14], plasma sulforaphane and metabolites in those eating cooked broccoli were one-tenth that of those eating raw broccoli.…”
Section: Introductionmentioning
confidence: 90%
“…[54][55][56] Broccoli that was fed raw had a higher sulforaphane concentration, as would be expected. 57 The maximum plasma thiocyanate value reported for smokers was 121 lM. 29 Choi et al 58 measured the concentrations of thiocyanate, cyanide, and organic isothiocyanates in the serum of rats after administration of a single dose of 50 lmol of various glucosinolates.…”
Section: Glucoraphanin Concentrations That Produce Beneficial Effectsmentioning
confidence: 99%